2019
DOI: 10.1016/j.toxrep.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mutagenicity of gas-vapour phase extracts from flavoured and unflavoured heated tobacco products

Abstract: The in vitro mutagenic and genotoxic potential of Heated Tobacco Products (HTPs) has already been studied with the particulate phase and reported previously. This study has been designed to complement the in vitro assessment of the HTP and to determine whether the inclusion of potential flavourings would alter the in vitro response by testing the other phase of the aerosol, the gas-vapour phase (GVP). Both flavoured and unflavoured Neostik GVP samples did not show any sign of mutagenic activity in the Ames tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…This assessment paradigm is intended to be an important complement to the required regulatory safety toxicological data and is in line with the Tox21 framework [6], which advocates the use of high-throughput methods to generate mechanistic data. For example, a recent study used regulatory safety toxicological tests to assess whether addition of flavoring substances to an unflavored product contributes to the toxicity of the gas–vapor phase [7]. Such tests can now also be conducted by using more advanced whole-aerosol exposure systems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This assessment paradigm is intended to be an important complement to the required regulatory safety toxicological data and is in line with the Tox21 framework [6], which advocates the use of high-throughput methods to generate mechanistic data. For example, a recent study used regulatory safety toxicological tests to assess whether addition of flavoring substances to an unflavored product contributes to the toxicity of the gas–vapor phase [7]. Such tests can now also be conducted by using more advanced whole-aerosol exposure systems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the cytotoxicity and the biological roles of e liquids, several studies have appeared in the literature during the last decade. To begin with, a relevant study reported the capacity of electronic cigarette to be approximately 10 fold less toxic in an in vivo model than conventional cigarettes [ 54 ], whereas it has also been demonstrated that the electronic cigarettes are less mutagenic that conventional ones [ 55 ]. So far, many different flavoring substances with different flavor composition and concentration are used in e-liquids [ 56 ], as it has also been analysed with chormatographic tools [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This section of the review will not discuss those studies which have characterised flavour ingredients present in heated tobacco products (including menthol) (Reger et al, 2018;Jaccard et al, 2019a) or investigated their transfer rates to aerosol (Czégény et al, 2016;Blazsó et al, 2018). Toxicological studies have suggested that the presence of flavour ingredients does not modify the in vitro effects of heated tobacco product aerosols (Crooks et al, 2018;Le Godec et al, 2019). Nevertheless, separate authors have indicated a need for additional research on flavour ingredients in heated tobacco products (Kaur et al, 2018).…”
Section: Aerosol Chemistrymentioning
confidence: 99%
“…With respect to those mammalian assays which are used to investigate cytogenetics/mutation [micronucleus assay and mouse lymphoma assay], several heated tobacco products including the EHCSS, EHCSS Series K, THS 2.2 and THP 1.0 have been assessed using these assays (Schramke et al, 2006;Roemer et al, 2008;Werley et al, 2008;Schaller et al, 2016a;Crooks et al, 2018;Thorne et al, 2018Thorne et al, , 2019aThorne et al, , 2019bThorne et al, , 2020Le Godec et al, 2019;Wang H et al, 2021). The results from these studies indicated that total particulate matter, the gas/vapour phase and/or whole aerosol produced from heated tobacco products either demonstrate an absence of genotoxicity under the conditions of test or a significant reduction in genotoxicity when compared to conventional cigarettes in both assays.…”
Section: Neutral Red Uptake Assay (Mammalian Cytotoxicity Assay)mentioning
confidence: 99%